2012
DOI: 10.1002/pmic.201200228
|View full text |Cite
|
Sign up to set email alerts
|

Carbon source‐induced reprogramming of the cell wall proteome and secretome modulates the adherence and drug resistance of the fungal pathogen Candida albicans

Abstract: The major fungal pathogen Candida albicans can occupy diverse microenvironments in its human host. During colonization of the gastrointestinal or urogenital tracts, mucosal surfaces, bloodstream, and internal organs, C. albicans thrives in niches that differ with respect to available nutrients and local environmental stresses. Although most studies are performed on glucose-grown cells, changes in carbon source dramatically affect cell wall architecture, stress responses, and drug resistance. We show that growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
143
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 89 publications
7
143
1
Order By: Relevance
“…Moreover, the available carbon source regulates morphogenesis, cell wall structure and stress responses (22,71,72). Catabolism of amino acids, which appear to be readily available in many host niches, also strongly affects the interaction of C. albicans with the host, by allowing the pathogen to modulate the surrounding pH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the available carbon source regulates morphogenesis, cell wall structure and stress responses (22,71,72). Catabolism of amino acids, which appear to be readily available in many host niches, also strongly affects the interaction of C. albicans with the host, by allowing the pathogen to modulate the surrounding pH.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that growth of C. albicans cells on lactate instead of glucose significantly alters the conformation of mannan fibrils on the cell surface as well as the expression of cell wall and secreted proteins (12,14). As cell surface mannoproteins are the first point of direct contact between the pathogen and innate immune cells, we examined the impact of alternative carbon source assimilation upon host immune responses.…”
Section: Growth Of C Albicans Cells On Lactate Dampens Their Stimulamentioning
confidence: 99%
“…We show that growth on this alternative carbon source significantly affects cytokine production by peripheral blood mononuclear cells (PBMCs) and macrophages, the phagocytosis of C. albicans by these cells, and the ability of C. albicans to escape and kill macrophages. Our studies underline the importance of carbon source for fungal virulence, indicating that in addition to modulating the physiological status of the fungus (12,14,30,31), carbon source has a distinct effect on the host-fungus interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 The food source used by Candida in a particular niche is not a trivial detail, as studies have clearly indicated the effects of environmental cues, such as nutrient availability, on cell wall architecture [43][44][45] which impacts interactions between Candida and immune cells. Recent in vitro work has shown that in the presence of lactic acid (as the sole carbon source) C. albicans is taken up by macrophages less efficiently and can alter immune cell cytokine profiles, specifically by increasing IL-10 and decreasing IL-17 production.…”
mentioning
confidence: 99%